Cicadas (Hemiptera: Cicadidae) from Camiguin of Mindanao Province and Dinagat Island in the Philippines, with a new genus and three new species - Lee, Young June; Marshall, David C.; Mohagan, Alma; Hill, Kathy B.r. (Zootaxa, 2016)
This paper provides the first faunal checklist for the family Cicadidae (Hemiptera) from Camiguin of Mindanao Province and Dinagat Island in the Philippines, comprising ten species belonging to nine genera. Cryptotympana shillana Lee & Mohagan sp. nov., Orientopsaltria inermis (Stål, 1870), Purana crassinotata Lee, 2015, and Huechys parvula Haupt, 1924 are recorded for the first time from Camiguin. Platypleura dinagatensis Lee sp. nov., Chremistica kyoungheeae Lee, 2010, Dundubia vaginata (Fabricius, 1787), Oncotympana pallidiventris Stål, 1870, and Philipsalta nigrina Lee, Marshall & Hill sp. nov. are newly recorded from Dinagat Island. A new genus Philipsalta Lee, Marshall & Hill gen. nov. is erected. Huechysini Distant, 1905 syn. nov. is synonymized with Cicadettini Buckton, 1889. Information on geographic distributions of the Camiguin and Dinagat species is also provided.